2009
DOI: 10.1002/app.29444
|View full text |Cite
|
Sign up to set email alerts
|

Friction and wear behavior of glass fabric/phenolic resin composites with surface‐modified glass fabric

Abstract: Untreated, air-plasma-bombarded, and b-aminoethyltrimethoxylsilane-silanized glass fabric (GF) was used to prepare GF/phenolic composites by dip coating in a phenolic adhesive resin and successive curing. The tribo-performances of these GF/phenolic composites sliding against AISI-1045 steel were evaluated with a pin-on-disc wear tester. The chemical composition of the untreated and surface-treated GF was analyzed with Fourier transform infrared spectroscopy and X-ray photoelectron spectroscopy. The interfacial… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
4
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 10 publications
(4 citation statements)
references
References 19 publications
0
4
0
Order By: Relevance
“…Hence, this technique has been extensively used in plastics, rubbers, composites, and adhesives. [1][2][3] The properties of the blend depend on the degree of compatibility or miscibility of the polymers at molecular mixing; blends can be classified as a compatible blend or completely miscible and incompatible or immiscible blends. [4][5][6] The polymer miscibility is due to some specific interactions such as dipole-dipole forces, hydrogen bonding, and charge transfer complex between the polymer segments.…”
mentioning
confidence: 99%
“…Hence, this technique has been extensively used in plastics, rubbers, composites, and adhesives. [1][2][3] The properties of the blend depend on the degree of compatibility or miscibility of the polymers at molecular mixing; blends can be classified as a compatible blend or completely miscible and incompatible or immiscible blends. [4][5][6] The polymer miscibility is due to some specific interactions such as dipole-dipole forces, hydrogen bonding, and charge transfer complex between the polymer segments.…”
mentioning
confidence: 99%
“…Many papers have reported that phenolic-matrix composites exhibit excellent synergistic effects on mechanical and tribological properties. Different reinforcements, such as glass fibers/fabric, carbon fibers [ 6 ], ceramic nanoparticles, graphene, and soft metals, have been used to promote tribological properties [ 7 , 8 ]. Suitable interfacial bonding, such as surface modification, including acid etching, plasma bombardment, and chemical grafting, is needed to improve the tribological properties of phenolic composites [ 6 , 7 , 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, the aggregation of BN increases the roughness, and the particles can be easily pulled out [ 9 ]. Combining physical interactions with chemical interactions between reinforcements and resin can improve the tribological behavior of polymer composites [ 8 ]. Many methods, such as the introduction of an interfacial linker and plasma treatment, provide strong interlock forces and chemical interactions in the interphase [ 6 , 11 ].…”
Section: Introductionmentioning
confidence: 99%
“…30 Combining fillers with UHMWPE fabric requires a basic matrix, which is commonly resin, such as epoxy 31 and phenolic resins. 32 However, due to the low-surface energy of UHMWPE fiber and lack of polar functional groups, its surface is smooth and inert, such adhesion between fabric and matrix is not ideal. 33 Due to low-interfacial bonding forces, composites need to be modified before sizing and bonding.…”
mentioning
confidence: 99%